Online community management for dummies - Ng, Deborah (John Wiley & Son, 2012)
This straightforward-but-fun guide shows you how to effectively manage, grow, and communicate with your online community. Clear coverage shares tips for dealing with customers and fans through Twitter, Facebook, forums, and blogs.